Physical, Mechanical, and Antioxidant Properties of Edible Film from Jackfruit Seed Starch and Microcellulose with Addition of Green Tea Extract - Kemala, Tetty; Nada, Nida Kotrun; Arifin, Budi (Universitas Andalas, 2025)
Edible films are gaining popularity as biodegradable alternatives to plastic packaging. Starch-microcellulose-based edible films are known to exhibit favorable physical and mechanical properties. However, enhancing their resistance to deterioration as food packaging is essential for extending shelf life of the product. This study aimed to develop edible films from jackfruit seed starch and microcellulose with the incorporation of green tea extract and to evaluate its effects on the films’ antioxidant activity, physical, and mechanical properties. Edible films were prepared with green tea extract at concentrations of 2.5%, 5%, 7.5%, and 10% (w/w of total starch). The produced films exhibited a smooth and elastic texture. The addition of green tea extract enhanced antioxidant properties, as indicated by an increase in 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, with the highest activity observed at 10% extract concentration. Furthermore, the extract improved the films' thickness, density, tensile strength, and elongation while reducing water absorption and water vapor transmission rate. However, the mechanical properties did not yet meet the Indonesian National Standard for packaging materials.